El Necrologi de Sant Miquel d'Escornalbou (Nova YorK, Hispanic Society of America, ms. B2715) - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2005)
The New York Hispanic Society of America manuscript is the only piece that has survived from the ancient library of the community of Augustinian canons of Sant Miquel d?Escornalbou in the Baix Camp de Tarragona county, founded by King Alfons I the Chaste in 1162. It is a martyrology by Usard, preceded by the necrology published in this volume. This text, started in 1196-1199, is an unavoidable source to know the history of the canonical community that is at its origin.